EVALUASI PROSEDUR PENGELUARAN KAS DENGAN MENGGUNAKAN UANG PERSEDIAAN PADA DINAS PENDAPATAN DAERAH KOTA MANADO - Dendeng, Windy Firginia; Elim, Inggriani; Wokas, Heince Rudy Nicky (GOING CONCERN : JURNAL RISET AKUNTANSI, 2020)
The implementation of a government system that is synergic and fair with the principle of decentralization requires the existence of a financial management that is accountable and transparent. Evaluation of cash disbursement procedures for money supply is a form of financial management that is accountable and transparent. Inventory money is the initial fund given to the regional government SKPD at the beginning of the fiscal year as an advance for the implementation of SKPD operational activities. The purpose of this study was to evaluate the implementation of the procedure for the issuance of cash in cash inventories in the regional income department of the city of Manado. The analytical method used in this research is descriptive analysis method. The results showed that the implementation of the procedure for issuing cash in the form of cash in the regional income department of the city of Manado was not yet effective and was not in accordance with SE.900 / 316 / BAKD because some supporting documents required by law were not attached and for the use of money the supplies still needed control and supervision in accordance with regulation number 60 of 2008 concerning the government's internal control system.